Status of Lymph Node Micrometastasis Via Immunohistochemical Staining and Related Factors in Gastric Cancer Undergoing Curative Surgery - Dinh Dat, Nguyen; Thi Vuong, Nguyen; Van Thang, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 40 No 3DO - 10.25073/2588-1132/vnumps.4637, 2024)
Aim: To describe the status of lymph node micrometastasis using immunohistochemistry in gastric cancer patients who underwent curative surgery and were determined to have no lymph node metastasis based on conventional HE staining. Methods: A retrospective descriptive study. Study Subjects: The subjects include gastric cancer patients who underwent curative surgery and were confirmed as N0 based on routine pathology from May 2022 to May 2024 at Hanoi Medical University Hospital. Results: The rate of lymph node micrometastasis was identified in 9 out of 44 patients (20.5%). Patients with poorly differentiated histological types, lymphovascular, and perineural invasion had a statistically significant higher rate of lymph node micrometastasis compared to the other group (p = 0.012 < 0.05). Conclusion: The rate of lymph node micrometastasis in the study was 20.5%, and patients with poorly differentiated histological types, vascular, and neural invasion had a significantly higher rate of lymph node micrometastasis compared to the other group.